Colistin-induced autophagy and apoptosis involves the JNK-Bcl2-Bax signaling pathway and JNK-p53-ROS positive feedback loop in PC-12 cells. (1st November 2017) - Lu, Ziyin; Miao, Yusong; Muhammad, Ishfaq; Tian, Erjie; Hu, Wanjun; Wang, Jian; Wang, Bo; Li, Rui; Li, Jichang
Abstract: Our recent study demonstrated neurotoxicity of colistin-induced autophagy and apoptosis in PC-12 cells, and that autophagy reached peak level at 12 h. In this study, we scrutinized the role of JNK in colistin-induced neurotoxicity and demonstrated the relationship among JNK, p53 and ROS in colistin treated PC-12 cells. Colistin-induced autophagy and apoptosis by JNK inhibition/activation were examined by western blotting, electron microscopy, and immunofluorescence/fluorescence microscopy. The results indicated that colistin induced JNK activation reached peak level at 12 h, while the highest levels of p -Bcl2/Bcl2 were observed at 12 h and Bax/Bcl2 significantly increased in a time-dependent manner. In PC-12 cells, inhibition of JNK by SP600125 (JNK inhibitor) resulted in significantly lower levels of autophagy upon colistin treatment, depending on the expression levels of Beclin1, LC3-II, p62 degradation and reduction in the number of autophagic vacuoles. In contrast, anisomycin pretreatment PC-12 cells led to upregulated autophagy. Especially, the highest levels of Beclin1 and p -Bcl2/Bcl2 were observed at 6 h, and Bax/Bcl2, cleaved-caspase3 and cleaved-PARP significantly increased in a time-dependent manner. The results revealed that JNK activation mediated autophagy and apoptosis related to Beclin1-Bcl2 and Bax-Bcl2 complex in colistin-treated PC-12 cells. Silencing of p53 by siRNA before colistin treatment substantially reduced ROS production and transactivated JNK in PC-12 cells. Moreover, activation of JNK increased ROS generation in PC-12 cells. In conclusion, colistin-induced autophagy and apoptosis is correlated to JNK-Bcl2-Bax signaling pathway, and an interaction effect found between intracellular ROS level and JNK-p53 signaling pathway in apoptosis. Highlights: JNK signaling pathway mediates colistin-induced autophagy and apoptosis. Colistin-induced autophagy and apoptosis is correlated to JNK-Bcl2-Bax signaling pathway. ROS-JNK-p53 positive feedback loop was involved in autophagy and apoptosis.